Application of Constructivism Theory-Based Learning Model in Qur'an Hadith Lessons at Al-Jihad Junior High School Surabaya - M Dzikrul Hakim Al Ghozali; Azizah Ashari (APPLICATION: Applied science in Learning Research, 2021)
This study aims to determine the application of constructivism learning theory in the Qur'an Hadith lessons at Al-Jihad Junior High School Surabaya. This research is expected to make a new contribution to the learning of the Qur'an and Hadith in general, and in particular to Al-Jihad Junior High School Surabaya as the school used for the research. The research approach used is qualitative with the type of case study research. The data generated from the qualitative method are in the form of descriptive narratives of written words or verbal statements from sources and people who have been determined by the researcher in advance. Data collection methods in this study were observation, interviews and documentation. The location of this research is in Al-Jihad Junior High School Surabaya. The subjects in this study were in the teacher's room and classroom, for the informants studied were teachers of all PAI subjects who also served as principals and students of Al-Jihad Junior High School Surabaya. The approach applied in learning the Qur'an Hadith is a constructivist learning theory that is useful for training students' independence, supported by various methods, namely the teacher makes small groups then gives a problem to discuss, the teacher plays a video in the form of a short film then the students conclude, the teacher invites students leave the classroom to do learning, the teacher invites students to play games in the classroom. Thus it will become social interaction in the classroom and psychologically will have a good impact on students if this method works well, the teacher is only a facilitator and mediator, the relationship between the teacher and students is as a partner who learns together.